Identification of E-commerce Solutions in Procurement and Sales Processes Polish Perspective - Tomasz BOBER (Communications of International Proceedings, 2025)
The main goal of the article is to present the results of research in the field of e‑commerce solutions in procurement and sales processes. Its purposes moreover are to disseminate existing studies, to identify solutions used in practice, prospects for their development in the future, as well as setting new directions for research. The observed trends and adaptation processes have been visible in the economy for a long time, but the Covid-19 pandemic accelerated them. However, the durability of changes in consumer behavior remains an important question.  Research methods: Literature review combined with the conceptualization and critical evaluation of existing approaches. The essence of the study is the identification of modern technological solutions used in logistics, which are elements of widely understood e-commerce.  In the light of current research, the growing role of solutions such as Dropshipping and Fulfillment can be observed, and the Strategic Sourcing concept can bring real benefits to the company, but it means changing processes both within the company and closer cooperation and integration of IT systems throughout the entire supply chain. In conclusion, it can be stated that the introduction of e-commerce requires changes in business management, primarily in the IT area, but also the definition of new strategic challenges.
Keywords: logistics; e-commerce; dropshipping; fulfillment; strategic sourcing; supply chain management